Synthesis, characterization, molecular docking and anticancer studies of fluoroaniline derivatives of hydroxybenzoquinone and hydroxynaphthoquinone. Issue 9 (23rd May 2022) - B., Arunkumar; Fernandez, Annette; Laila, Shiny P.; Nair, Achuthsankar S.; Vishnu, V. S.
Abstract: Two series of fluoro substituted-anilino derivatives of naturally occurring hydroxybenzoquinone and hydroxynaphthoquinone were synthesized using TFA as catalyst to improve the product yield. Recently, fluorine containing compounds are being used as anticancer drugs. The aim of this study is to find compounds that are active against melanoma cells. This six new fluoro substituted quinone compounds were synthesized and characterized. All of these compounds were then subjected to molecular docking studies against B-raf protein using Discovery Studio 4.0 and the binding affinities were calculated. The energy scores of in silico analysis revealed that all the compounds exhibited better binding affinity towards B-raf protein. Moreover, all the derivatives and the parent compounds, embelin and plumbagin along with standard drug, PLX4032 were investigated for its in vitro cytotoxicity in A375 cell lines (Melanoma) and in vitro ELISA assay in B-raf isolated from melanoma cells. Among them, 5-(3-chloro-4-trifluoromethoxy-phenylamino)-2-hydroxy-3-undecyl-[1, 4]benzoquinone exhibited lower cell viability with lowest LC50 of 12.25 μg/mL and thus poses suitability to be a lead molecule for further drug discovery. Communicated by Ramaswamy H. Sarma